2016
DOI: 10.1186/s12944-016-0315-3
|View full text |Cite
|
Sign up to set email alerts
|

Significantly greater triglyceridemia in Black African compared to White European men following high added fructose and glucose feeding: a randomized crossover trial

Abstract: BackgroundBlack African (BA) populations are losing the cardio-protective lipid profile they historically exhibited, which may be linked with increasing fructose intakes. The metabolic effects of high fructose diets and how they relate to blood lipids are documented for Caucasians, but have not been described in BA individuals.ObjectiveThe principle objective of this pilot study was to assess the independent impacts of high glucose and fructose feeding in men of BA ancestry compared to men of White European (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Our results may differ as this is one of the few studies to exclusively comprise adult men rather than children/adolescents 18,19,37,38,40 or all-female cohorts. 39,[41][42][43][44][45] Two other adult nondiabetic all-male studies have examined ethnic differences in insulin responses 46,47 ; neither found increased insulin secretion in subjects of African ancestry compared with white subjects, consistent with our findings. It is worth considering that the paucity of male participants in this area of the literature may have led to an overestimation of ethnic differences in insulin secretory response.…”
Section: Discussionsupporting
confidence: 90%
“…Our results may differ as this is one of the few studies to exclusively comprise adult men rather than children/adolescents 18,19,37,38,40 or all-female cohorts. 39,[41][42][43][44][45] Two other adult nondiabetic all-male studies have examined ethnic differences in insulin responses 46,47 ; neither found increased insulin secretion in subjects of African ancestry compared with white subjects, consistent with our findings. It is worth considering that the paucity of male participants in this area of the literature may have led to an overestimation of ethnic differences in insulin secretory response.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, decreased lipid clearance can be caused by sucrose (Grant, Marais, & Dhansay, ) and fructose (Jeppesen et al, ). Increased circulating TG with fructose in the diet was also seen in human males (Bantle et al, ; Goff, Whyte, Samuel, & Harding, ), but not in females (Bantle et al, ). Moreover, as in our study, no differential effects on hepatic TG levels were seen in humans with 25 energy percent from glucose or from fructose, neither with isocaloric feeding nor hypocaloric feeding (Johnston et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…The characteristics of the included studies are shown in Table 1. The majority were studies of African American populations ( n = 30), but other study populations included indigenous black African ( n = 5) [2428], immigrant black African ( n = 2) [29, 30], UK African-Caribbean ( n = 3) [3133], and a mixture of the above ( n = 1) [34]. The total number of subjects of BA ethnicity in the included studies was 4619.…”
Section: Resultsmentioning
confidence: 99%
“…The studies comprised 17 all-female cohorts [25–28, 37, 41, 43, 4856], 3 all-male cohorts [24, 29, 30], and 21 mixed-sex cohorts. Where sex of subject was reported by ethnicity, the majority in both BA (3350 of 4395, or 76%) and WE (6630 of 10900, or 61%) subjects were female.…”
Section: Resultsmentioning
confidence: 99%